Application Mass Spectrum Method in Determination Compound Bioactive of The Essential Oil from Leaves and Stems of Clove (Syzigium aromaticum) - Rifai, Akhmad; Riyadi, Nur Amin (INTEK: Jurnal Penelitian, 2021)
The essential oil from leaves and stems of clove (Syzigium Aromaticum) growing in Siwa (South Sulawesi, Indonesia), was obtained by hydrodistillation and gas chromatography-mass spectrometry (GC-MS) was used to identify the constituent of the sample. There were five most compounds bioactive contained in the clove oil of the leaves and stems, namely eugenol, b-caryophyllene, 1,4,7- cycloundecatriene-1,5,9,9 tetramethyl, caryophyllene oxide, and cadinene. The eugenol compound, which is contained in the stems is 55.83% bigger than the leaves, which is 45.3%. But on the contrary, other compounds in the leaves are b-caryophyllene (25.57%), 1,4,7- cycloundecatriene-1,5,9,9 tetramethyl (8.65%), caryophyllene oxide (4.64%) and cadinene (2.31%) greater than the other compounds in the stems, namely b-caryophyllene (19.72%), 1,4,7- cycloundecatriene-1,5,9,9 tetramethyl (4.38%), caryophyllene oxide (3.48%) and cadinene (0.5%). Eugenol is the major constituent of the clove oil that can be used in pharmacology as antivirus, antimicrobial, antiseptic, and industry of perfume.